2015
DOI: 10.1080/1369183x.2015.1073578
|View full text |Cite
|
Sign up to set email alerts
|

‘I think I'm more free with them'—Conflict, Negotiation and Change in Intergenerational Relations in African Families Living in Britain

Abstract: While the family is increasingly being recognised as pivotal to migration, there remain too few studies examining how migration impacts on intergenerational relationships. Although traditional intergenerational gaps are intensified by migration, arguably there has been an over-emphasis on the divisions between 'traditional' parents and 'modern' children at the expense of examining the ways in which both generations adapt. As Foner and Dreby stress (2011), the reality of post-migration intergenerational relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…As found, parents often experienced parenting as difficult and pointed to “knowledge gaps” in their community. As indicated by the topics discussed among parents in the programme, questions about children's developmental transition in puberty; societies' digitalization; cultural transmission (Cook & Waite, ; De Haan, ; Renzaho et al, ); and issues of discrimination and exclusion intersecting with low socio‐economic status (Hermans, ) add up to this. Handling these challenges may become strained postmigration due to eroded social networks and an often experienced shift from collective to individual parenting culture postmigration (De Haan, ; Renzaho et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As found, parents often experienced parenting as difficult and pointed to “knowledge gaps” in their community. As indicated by the topics discussed among parents in the programme, questions about children's developmental transition in puberty; societies' digitalization; cultural transmission (Cook & Waite, ; De Haan, ; Renzaho et al, ); and issues of discrimination and exclusion intersecting with low socio‐economic status (Hermans, ) add up to this. Handling these challenges may become strained postmigration due to eroded social networks and an often experienced shift from collective to individual parenting culture postmigration (De Haan, ; Renzaho et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…As found, parents often experienced parenting as difficult and pointed to "knowledge gaps" in their community. As indicated by the topics discussed among parents in the programme, questions about children's developmental transition in puberty; societies' digitalization; cultural transmission (Cook & Waite, 2016;De Haan, 2011;Renzaho et al, 2011); and issues of discrimination and exclusion intersecting with low socio-economic status (Hermans, 2004) This study illustrates how this approach shifts our view on parents as being "in need of certain skills and knowledge" to being "learning resources for one another". This is of extra importance in settings in which issues of diversity, inclusion, and social justice are of great concern for professional development in social work fields (Bose, 2014).…”
Section: Findings Indicate Fathers' Relatively New Experience With Comentioning
confidence: 96%
See 1 more Smart Citation
“…Parenting practices of African immigrants are highly gendered, with the sex of both the child and the parent being a key determinant of parenting practices (J. Cook & Waite, 2016;Phillips-Mundy, 2011). Although African parents often adapt their disciplinary practices to different societal norms following migration, they tend to retain some cultural practices, including the use of corporal discipline (e.g., spanking), that can trigger acrimonious parent-child relationships.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the authors found only one study on tensions in parent-child relations among African immigrant families in Britain (J. Cook & Waite, 2016), and none in Canada, despite the surge in the African immigrant population in the country. To address this gap, we conducted a critical ethnographic study of African immigrant parenting practices in Alberta, Canada.…”
mentioning
confidence: 99%